Numerical Investigation of the Emission Features in a Vortex Flameless Combustor - Abdelgader A.S. Gheidan; Mazlan Bin Abdul Wahid; Rahel G. Rahel; Lei Li; Muhammad Amri Mazlan; Anthony C. Opia; Najib Aminu Ismail (Science and Technology: Developments and Applications Vol. 1, 2024)
Various pollutants, including unburned hydrocarbon, carbon dioxide (CO2), carbon monoxide (CO), nitride oxide (NOx), soot, and particulate matter, are typically discharged into the air during combustion. Currently, minimizing these unhealthy emissions during combustion and conserving energy are two prevailing problems faced in the creation of modern combustion systems and the energy conversion process. This study numerically investigates the effects of air/fuel configurations on NOx emission control during methane combustion at varying thermal intensities. Computational Fluid Dynamics (CFD) Modelling developed for this numerical analysis is based on the combustor geometry which can be used as an asymmetric combustor with tangential air inlets and axial air and fuel inlets as shown. The analysis focuses on small-scale combustor structures influenced by various combustion factors, employing diverse air and fuel injection configurations to explore distinct combustion characteristics. In reverse configuration modes, the air injection port is located at the combustor exit, whereas in forward configurations, the air injection port is placed at the opposite end of the combustor, with a corresponding change in fuel position. The findings reveal that both non-premixed and premixed combustion modes produce exceptionally low NOx emissions. Notably, premixed combustion in forward and reverse flow configurations (FP and RP) achieves significantly lower NO and CO emissions compared to non-premixed configurations across all equivalence ratios (\(φ\)). The study highlights that changes in fuel injection position affect mixture preparation, often resulting in premature combustion with reduced emissions, although occasional hot spots and increased emissions are observed. The reverse-cross-flow configuration (RC1) demonstrated superior performance, achieving the lowest NO emissions (approximately 1.30E-05 ppm) and CO emissions (approximately 223 ppm) compared to other configurations (RC2 and RC3). Additionally, the analysis shows that smaller combustor volumes, while promoting high thermal intensities (324–393 MW/m3·atm), lead to reduced residence times, limited gas recirculation, and elevated CO and NOx emissions. These findings offer valuable insights into optimizing air/fuel configurations for efficient and environmentally friendly combustion.